The Effect Of Using Duolingo To Improve Students’ Vocabulary Mastery At The Eleventh Grade Students Of SMAN 5 Pinggir - Suci Oktarini, Dwi (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2023)
This study was a quantitative approach with quasi-experimental research design. The descriptive quantitative methods was applied to describe the data.. The population of the study was eleventh grade students especially social studies class with a total of 81 students, consisting of 3 classes. Due to the large number of population, the researcher took a sample of 57 students. In this research, it was found that the mean of pre-test score in experimental class was 64 and in control class was found 60.14. Meanwhile, the mean of post-test score which found in experimental class was 75.31 and in control class was 68.14. It can be concluded that there were differences in the average of the students’ vocabulary in speaking at the time of pretest and posttest. It meant there was significant effect on students’ vocabulary